2018
DOI: 10.1073/pnas.1722043115
|View full text |Cite|
|
Sign up to set email alerts
|

B7-H1 maintains the polyclonal T cell response by protecting dendritic cells from cytotoxic T lymphocyte destruction

Abstract: Induced B7-H1 expression in the tumor microenvironment initiates adaptive resistance, which impairs immune functions and leads to tumor escape from immune destruction. Antibody blockade of the B7-H1/PD-1 interaction overcomes adaptive resistance, leading to regression of advanced human cancers and survival benefits in a significant fraction of patients. In addition to cancer cells, B7-H1 is expressed on dendritic cells (DCs), but its role in DC functions is less understood. DCs can present multiple antigens (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…Specifically, cDC1s, which are particularly important for the priming and activation of CD8 + T cells, upregulate PD-L1 expression upon antigen uptake. Consistent with a recent study, we found that PD-L1 on DCs protects them from killing by cytotoxic T lymphocytes, yet dampens the antitumor immune responses 37 . In addition, PD-L1 upregulation on cDC1s is mediated by IFN-γ produced by activated T cells.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, cDC1s, which are particularly important for the priming and activation of CD8 + T cells, upregulate PD-L1 expression upon antigen uptake. Consistent with a recent study, we found that PD-L1 on DCs protects them from killing by cytotoxic T lymphocytes, yet dampens the antitumor immune responses 37 . In addition, PD-L1 upregulation on cDC1s is mediated by IFN-γ produced by activated T cells.…”
Section: Discussionsupporting
confidence: 92%
“…In the context of these observations, it seems reasonable to combine local therapies with anti-PD therapy to neutralize the immunosuppressive mechanisms developed in the TME as long as the B7-H1/PD-1 pathway is one of the major immunosuppressive mechanisms. It is also possible that this combination may deviate the T cell response against viral antigens instead of tumor antigens due to possible immunological dominancy by anti-PD therapy (Martínez-Usatorre et al, 2018; Chen et al, 2018). Local treatment, on the other hand, has shown to be an effective approach to increase T cell infiltration into tumors.…”
Section: The Principles To Combine Other Therapeutics With Anti-pd Thmentioning
confidence: 99%
“…Следует отметить, что роль В7-Н1 в биологии DC до конца не ясна. Показано, в частности, что молекула В7-Н1, ýкспрессируемая на DC, участвует не только в индукции апоптоза и анергии Т-клеток [18], но обладает также протективной функцией, обеспечивая устойчивость DC к лизису со стороны цитотоксических Т-клеток [19]. В настоящем исследовании подавляющая часть интактных CD16 − Мо-DC и CD16 + Мо-DC коýкспрессировали В7-Н1 и CD86 (см.…”
Section: Discussionunclassified